Extrachromosomal elements in tobacco plastids. - Staub, J M (1994)
The plastid genome of higher plants is a circular double-stranded DNA molecule which is present in multiple identical copies. We report here an 868-bp plastid DNA minicircle, NICE1, that formed in tobacco (Nicotiana tabacum) plastids during transformation, as an unexpected product of homologous recombination. Such extrachromosomal elements are normally absent in plastids of higher plants. We have constructed shuttle plasmids containing NICE1 sequences which are maintained extrachromosomally when reintroduced into plastids by particle bombardment. Furthermore, recombination between homologous sequences in the shuttle plasmids and the main plastid genome occurs. Recombination products were characterized after recovery of the shuttle plasmids in Escherichia coli and of recombinant plastid genomes in the progeny of transformed plants. Our findings indicate that shuttle plasmids can be used to engineer plastid genes without concomitant integration of foreign DNA and to recover plastid mutations in E. coli.